Cellulose based cationic adsorbent fabricated via radiation grafting process for treatment of dyes waste water. (5th November 2015) - Goel, Narender Kumar; Kumar, Virendra; Misra, Nilanjal; Varshney, Lalit
Highlights: The textile cotton cellulose waste was transformed in to a functional adsorbent for treatment of textile dye wastewater. A green synthesis route, viz. one step-aqueous based radiation grafting process was employed. Critical scientific analysis of equilibrium and kinetic dye adsorption experimental data presented. Recyclable radiation grafted adsorbent offers a promising method for treatment of textiles dye effluents. Abstract: A cationized adsorbent was prepared from cellulosic cotton fabric waste via a single step-green-radiation grafting process using gamma radiation source, wherein poly[2-(methacryloyloxy) ethyl]trimethylammonium chloride (PMAETC) was covalently attached to cotton cellulose substrate. Radiation grafted (PMAETC- g -cellulose) adsorbent was investigated for removal of acid dyes from aqueous solutions using two model dyes: Acid Blue 25 (AB25) and Acid Blue 74 (AB74). The equilibrium adsorption data was analyzed by Langmuir and Freundlich isotherms, whereas kinetic data was analyzed by pseudo first order, pseudo second order, intra particle diffusion and Boyd's models. The PMAETC- g -cellulose adsorbent with 25% grafting yield exhibited equilibrium adsorption capacities of ∼540.0 mg/g and ∼340.0 mg/g for AB25 and AB74, respectively. Linear and nonlinear fitting of adsorption data suggested that the equilibrium adsorption process followed Langmuir adsorption isotherm model, whereas, the kinetic adsorption process followed pseudo-second order model. The multi-linearities observed in the intra-particle kinetic plots suggested that the intraparticle diffusion was not the only rate-controlling process in the adsorption of acid dyes on the adsorbent, which was further supported by Boyd's model. The adsorbent could be regenerated by eluting the adsorbed dye from the adsorbent and could be repeatedly used.